Mapping the anti-vaccination movement on Facebook. Issue 9 (29th July 2019) - Smith, Naomi; Graham, Tim
ABSTRACT: Over the past decade, anti-vaccination rhetoric has become part of the mainstream discourse regarding the public health practice of childhood vaccination. These utilise social media to foster online spaces that strengthen and popularise anti-vaccination discourses. In this paper, we examine the characteristics of and the discourses present within six popular anti-vaccination Facebook pages. We examine these large-scale datasets using a range of methods, including social network analysis, gender prediction using historical census data, and generative statistical models for topic analysis (Latent Dirichlet allocation). We find that present-day discourses centre around moral outrage and structural oppression by institutional government and the media, suggesting a strong logic of 'conspiracy-style' beliefs and thinking. Furthermore, anti-vaccination pages on Facebook reflect a highly 'feminised' movement ‒ the vast majority of participants are women. Although anti-vaccination networks on Facebook are large and global in scope, the comment activity sub-networks appear to be 'small world'. This suggests that social media may have a role in spreading anti-vaccination ideas and making the movement durable on a global scale.